Development of a hydrogel-based three-dimensional (3D) glioblastoma cell lines culture as a model system for CD73 inhibitor response study - Bahraminasab, Marjan; Asgharzade, Samira; Doostmohamadi, Ali; Satari, Atefeh; Hasannejad, Farkhonde; Arab, Samaneh (Biomedical engineering online, 2024)
Background Despite the development of various therapeutic approaches over the past decades, the treatment of glioblastoma multiforme (GBM) remains a major challenge. The extracellular adenosine-generating enzyme, CD73, is involved in the pathogenesis and progression of GBM, and targeting CD73 may represent a novel approach to treat this cancer. In this study, three-dimensional culture systems based on three hydrogel compositions were characterized and an optimal type was selected to simulate the GBM microenvironment. In addition, the effect of a CD73 inhibitor on GBM cell aggregates and spheroids was investigated as a potential therapeutic approach for this disease. Methods Rheology measurements, Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM) and cell proliferation assays were performed to analyze the synthesized hydrogel and select an optimal formulation. The viability of tumor cells in the optimal hydrogel was examined histologically and by confocal microscopy. In addition, the sensitivity of the tumor cells to the CD73 inhibitor was investigated using a cell proliferation assay and real-time PCR. Results The data showed that the hydrogel containing 5 wt% gelatin and 5 wt% sodium alginate had better rheological properties and higher cell viability. Therefore, it could provide a more suitable environment for GBM cells and better mimic the natural microenvironment. GBM cells treated with CD73 inhibitors significantly decreased the proliferation rate and expression of VEGF and HIF1-α in the optimal hydrogel. Conclusion Our current research demonstrates the great potential of CD73 inhibitor for clinical translation of cancer studies by analyzing the behavior and function of 3D tumor cells, and thus for more effective treatment protocols for GBM.